2013
DOI: 10.1002/dneu.22075
|View full text |Cite
|
Sign up to set email alerts
|

Two specific populations of GABAergic neurons originating from the medial and the caudal ganglionic eminences aid in proper navigation of callosal axons

Abstract: The corpus callosum (CC) plays a crucial role in interhemispheric communication. It has been shown that CC formation relies on the guidepost cells located in the midline region that include glutamatergic and GABAergic neurons as well as glial cells. However, the origin of these guidepost GABAergic neurons and their precise function in callosal axon pathfinding remain to be investigated. Here, we show that two distinct GABAergic neuronal subpopulations converge toward the midline prior to the arrival of callosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 105 publications
(164 reference statements)
0
24
0
Order By: Relevance
“…Our data support a role for commissural axons in neurophilic migration and, to the best of our knowledge, provide the first experimental evidence that commissural axonal fascicles act as border landmarks delimiting neuronal migration named 'axon-restricted migration'. Several studies have shown that conversely, appropriate clustering of cell bodies can influence the axon to be guided appropriately [7][8][9] . Furthermore, it is well established that both axons and neuronal cell bodies are influenced by direct chemotactic mechanisms 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data support a role for commissural axons in neurophilic migration and, to the best of our knowledge, provide the first experimental evidence that commissural axonal fascicles act as border landmarks delimiting neuronal migration named 'axon-restricted migration'. Several studies have shown that conversely, appropriate clustering of cell bodies can influence the axon to be guided appropriately [7][8][9] . Furthermore, it is well established that both axons and neuronal cell bodies are influenced by direct chemotactic mechanisms 5 .…”
Section: Discussionmentioning
confidence: 99%
“…As axons and neuronal cell bodies from different populations are guided simultaneously during development and are in close apposition, it seems plausible that forming axonal fascicles and cell bodies physically influence each other's behaviour. A small number of studies have shown that the position of cell bodies influence the guidance of axons by the production of chemotactic cues [7][8][9] . Conversely, there is also evidence to support the idea that pioneer axons provide a growth substrate for newly migrating axons and cell bodies [10][11][12] .…”
mentioning
confidence: 99%
“…Rather, transient neurons have been described during embryonic development and early postnatal stages (Niquille et al, 2009;Teissier et al, 2012) and, at least in the neocortex, it has been suggested that their death is regulated by intrinsically defined mechanisms (Southwell et al, 2012). Interestingly, these cells are often directed to white matter tracts, where they contribute to the guidance of growing axons (López-Bendito et al, 2006;Niquille et al, 2009Niquille et al, , 2013Sato et al, 1998). Moreover, these cells originate, in part, from the caudal ganglionic eminence, a major source of Sp8 + interneurons (Ma et al, 2012;Niquille et al, 2013).…”
Section: Fate Of the Newly Generated Neuroblastsmentioning
confidence: 99%
“…Interestingly, these cells are often directed to white matter tracts, where they contribute to the guidance of growing axons (López-Bendito et al, 2006;Niquille et al, 2009Niquille et al, , 2013Sato et al, 1998). Moreover, these cells originate, in part, from the caudal ganglionic eminence, a major source of Sp8 + interneurons (Ma et al, 2012;Niquille et al, 2013). These observations raise the possibility that the transient EC-LS neuroblasts belong to a broader population of cells involved in transient forms of plasticity, possibly related to the remodeling of long-range connections.…”
Section: Fate Of the Newly Generated Neuroblastsmentioning
confidence: 99%
“…Sources of these guidance cues include populations of guidepost cells (of both glial and neuronal identity) situated at various stages along the callosal tract. Examples of such populations are the indusium griseum at the midline dorsal border of the corpus callosum (Shu and Richards, 2001), the glial wedge ventral to the corpus callosum and medial to the lateral ventricles (Shu and Richards, 2001;Shu et al, 2003c), and the midline corridor, which lies ventral and dorsal to the corpus callosum at the midline (Silver et al, 1982;Shu et al, 2003b;Niquille et al, 2009;Niquille et al, 2013).…”
Section: Midline Crossingmentioning
confidence: 99%